Insights into the potential mechanism underlying liver dysfunction in male albino rat exposed to gasoline fumes. Issue 1 (1st January 2021) - Owagboriaye, Folarin; Aina, Sulaimon; Oladunjoye, Rasheed; Salisu, Titilola; Adenekan, Adedamola; Dedeke, Gabriel
ABSTRACT: The mechanism underlying the reported hepatotoxicity of gasoline fumes in experimental studies still remains unclear. In this study, we present insights into the mechanism underlying hepatotoxicity of gasoline fumes in 72 male albino rats. The rats were randomized into six groups. Group I (control) was exposed to distilled water while groups II, III, IV, V and VI were daily exposed to gasoline fumes for 1, 3, 5, 7 and 9 hours respectively for 10 weeks. Serum hepatic and oxidative stress markers, activity of the mixed function oxygenase (MFO) and membrane-bound ATPase enzymes in the liver as well as histopathological examination of the organ were monitored. Gasoline compositions and its residues in the liver were quantified with Gas Chromatography Mass Spectrometry. Significant (p < 0.05) alterations in the activities of all the enzymes, oxidative stress marker and MFO were observed in the exposed rats compared to control. A total of seventeen gasoline residues and metabolites were detected in the liver of exposed rats. Severe degenerative changes in the hepatic cells were seen in the exposed rats. Accumulation of gasoline residues and metabolites in the liver of exposed rats could potentially result in ROS production capable of inducing liver injury. GRAPHICAL ABSTRACT: uf0001